First case of evolved herbicide resistance in the holoparasite sunflower broomrape, Orobanche cumana Wallr. - Kaundun, Shiv Shankhar; Martin-Sanz, Alberto; Rodríguez, Maribel; Serbanoiu, Tiberiu; Moreno, Jose; Mcindoe, Eddie; le Goupil, Gael (Frontiers in Plant Science, 2024)
The development and commercialisation of sunflower varieties tolerant to acetolactate synthase (ALS)-inhibiting herbicides some 20 years ago provided farmers with an alternative method for the cost-effective control of Orobanche cumana. In 2020, however, two independent sunflower broomrape populations from Drama (GR-DRA) and Orestiada (GR-ORE), Greece, were reported to be heavily infested with O. cumana after application of the ALS-inhibiting herbicide imazamox. Here we have investigated the race of GR-DRA and GR-ORE and determined the basis of resistance to imazamox in the two Greek O. cumana samples.Using a set of five diagnostic sunflower varieties characterised by different resistant genes with respect to O. cumana infestation, we have clearly established that the GR-ORE and GR-DRA populations belong to the invasive broomrape races G and G+, respectively. Live underground tubercles and emerged shoots were identified at the recommended field rate of imazamox for GR-DRA and GR-ORE but not for two other standard sensitive populations in a whole plant dose response test using two different herbicide-tolerant sunflower hybrids as hosts.Sequencing of the ALS gene identified an alanine 205 to aspartate mutation in all GR-ORE samples. Most GR-DRA tubercles were characterised by a second serine 653 to asparagine ALS mutation whilst a few GR-DRA individuals contained the A205D mutation. Mutations at ALS codons 205 and 653 are known to impact on the binding and efficacy of imazamox and other imidazolinone herbicides. The knowledge generated here will be important for tracking and managing broomrape resistance to ALS-inhibiting herbicides in sunflower growing regions.